Long Run Risk, the Wealth-Consumption Ratio, and the Temporal Pricing of Risk - Koijen, Ralph S.J; Lustig, Hanno; Van Nieuwerburgh, Stijn; Verdelhan, Adrien (American Economic Review, 2010)
Long Run Risk, the Wealth-Consumption Ratio, and the Temporal Pricing of Risk by Ralph S. J. Koijen, Hanno Lustig, Stijn Van Nieuwerburgh and Adrien Verdelhan. Published in volume 100, issue 2, pages 552-56 of American Economic Review, May 2010